The Impact of Type 2 Diabetes Mellitus on Long-Term Prognosis in Patients of Different Ages with Myocardial Infarction - S. A. Afanasiev; A. A. Garganeeva; E. A. Kuzheleva; A. V. Andriyanova; D. S. Kondratieva; S. V. Popov (Journal of Diabetes Research)
The objective of the study was to assess the impact of DM2 at baseline on long-term mortality after acute myocardial infarction (MI) among different age groups. The data were taken from: “Register of Acute Myocardial Infarction.” A total of 862 patients were followed for five years after acute myocardial infarction. The primary endpoint was death from any cause. The patients were categorized into 2 groups based on their ages: group 1—comprised patients older than working age (n=358) and group 2—comprised employable patients (n=504). A total of 208 patients were diagnosed with both cardiovascular disease and DM2. Elderly patients with DM2 had worse prognosis and increased five-year mortality compared with patients of the same age group without DM2. Statistically significant differences in long-term outcomes were found in adult patients (p=0.004) only in group with longer duration of diabetes, unlike the group with DM2 onset. In conclusion, Type 2 DM increased 5-year mortality rate of elderly patients with myocardial infarction. However, younger patients with both myocardial infarction and DM2 had more complications in the early post-MI period compared with patients of the same age group without DM2 but did not show any statistically significant differences in the long-term outcome.